HIGH LEVEL THINKING ABILITY IN SOLVING HOTS QUESTIONS IN MATHEMATICS SUBJECTS - Sinaga, D. Yuliana (SENSEI RESEARCH CENTER, 2024)
required humans to have high level thinking skills. In the world of education, HOTS is the students’ thinking ability who do not only remember but also expected to be able to develop the ideas. This descriptive research aims to determine the ability to think at a higher level and to find out the obstacles in solving HOTS questions in mathematics on fifth grade students. The data was collected by giving a description test and interview to 90 students. The results of the PAP analysis on the final score of the test showed that 50 students (56%) had HOTS Thinking Ability was in the sufficient category. The next part through content analysis, the interview results showed that there were 61 students (68%) students had problems in the process of forming mathematic sentences. Based on this research, it could be concluded that the fifth grade students of SD Markus Medan tend to have sufficient HOTS thinking ability and were still low in answering questions with C6 cognitive domains, while the students' constraints were in the process of forming mathematic sentences. The conclusion obtained had implications in improving students' thinking abilities at each cognitive level through HOTS based assessment.